Hereditary myopathy with early respiratory failure: occurrence in various populations. Issue 3 (19th April 2013) - Palmio, Johanna; Evilä, Anni; Chapon, Françoise; Tasca, Giorgio; Xiang, Fengqing; Brådvik, Björn; Eymard, Bruno; Echaniz-Laguna, Andoni; Laporte, Jocelyn; Kärppä, Mikko; Mahjneh, Ibrahim; Quinlivan, Rosaline; et al.
Abstract : Objective: Several families with characteristic features of hereditary myopathy with early respiratory failure (HMERF) have remained without genetic cause. This international study was initiated to clarify epidemiology and the genetic underlying cause in these families, and to characterise the phenotype in our large cohort. Methods: DNA samples of all currently known families with HMERF without molecular genetic cause were obtained from 12 families in seven different countries. Clinical, histopathological and muscle imaging data were collected and five biopsy samples made available for further immunohistochemical studies. Genotyping, exome sequencing and Sanger sequencing were used to identify and confirm sequence variations. Results: All patients with clinical diagnosis of HMERF were genetically solved by five different titin mutations identified. One mutation has been reported while four are novel, all located exclusively in the FN3 119 domain (A150) of A-band titin. One of the new mutations showed semirecessive inheritance pattern with subclinical myopathy in the heterozygous parents. Typical clinical features were respiratory failure at mid-adulthood in an ambulant patient with very variable degree of muscle weakness. Cytoplasmic bodies were retrospectively observed in all muscle biopsy samples and these were reactive for myofibrillar proteins but not for titin. Conclusions: We report an extensive collection of families with HMERF with five different mutations in exon 343 of TTN, which establishes this exon as the primary target for molecular diagnosis of HMERF. Our relatively large number of new families and mutations directly implies that HMERF is not extremely rare, not restricted to Northern Europe and should be considered in undetermined myogenic respiratory failure.